PENDIDIKAN MULTIKULTURAL PADA PENDIDIKAN BAHASA DAN BUDAYA - Mifbakhuddin Mifbakhuddin (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2011)
Multiculturalism is an ideology and a tool to improve the human and humanity. To understand multiculturalism it is necessary needed a foundation of knowledge in the form of building concepts that are relevant and support the existence and functioning of multiculturalism in human life. In the last decade, the discourse of multiculturalism becomes an important issue in development of culture in Indonesia. What is the role of language to unite the nation? It begins by relating language to culture. Language and cultural education has a central role in growing nationalism. Especially in education, the role of language and culture can play a role in efforts to unite the nation. The role of language and culture in relation with nationalism is a function of unifying and separatist. Unifying function refers to the feelings of the members of a nationality that they gathered and identified with others who use the same language. The second function refers to the feelings of the members of the nationality that they are different and separate from those of other languages.